Back to basics in HIV prevention: focus on exposure. Issue 7403 (19th June 2003) - Pisani, Elizabeth; Garnett, Geoff P; Grassly, Nicholas C; Brown, Tim; Stover, John; Hankins, Catherine; Walker, Neff; Ghys, Peter D
Abstract : Despite worldwide efforts to prevent HIV infection, the number of people affected continues to rise. The authors of this article argue that a commonsense approach based on simple country by country analyses could improve the situation